Higher oxidized high-density lipoprotein to apolipoprotein A-I ratio is associated with high-risk coronary plaque characteristics determined by CT angiography. (1st February 2021) - Suruga, Kazuki; Miyoshi, Toru; Kotani, Kazuhiko; Ichikawa, Keishi; Miki, Takashi; Osawa, Kazuhiro; Ejiri, Kentaro; Toda, Hironobu; Nakamura, Kazufumi; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: Oxidized high-density lipoprotein (oxHDL), unlike native HDL, is characterized by reduced cholesterol efflux capability and anti-inflammatory properties. The ratio of oxHDL to apolipoprotein A-I (oxHDL/apoAI) is a possible marker of dysfunctional HDL. The aim of this study was to evaluate the association between oxHDL/apoAI and coronary plaque characteristics that increase the likelihood of cardiovascular events as determined by coronary computed tomography (CT) angiography. Methods: A total of 297 patients (mean age; 67 years, men; 63%) who underwent coronary CT angiography for suspected stable coronary artery disease (CAD) were included. High-risk plaques (HRP) were defined by three characteristics: positive remodeling; low-density plaques; and spotty calcification. Significant stenosis was defined as a luminal narrowing of >70%. Serum concentrations of oxHDL were measured using an enzyme-linked immunosorbent assay. Results: Patients with higher oxHDL/ApoAI showed significantly greater prevalence of HRP ( p  = 0.03) and significant stenosis ( p  < 0.01) compared with patients with low oxHDL/ ApoAI. The multivariate logistic analysis demonstrated that oxHDL/ApoAI significantly associated with the presence of HRP and significant coronary stenosis ( p  = 0.01 and < 0.01). In the follow-up study including 243 patients for a median period of 1.8 years, univariate cox regression analysis showed that oxHDL/ApoAI, HRP and significant stenosis were significant predictors of cardiovascular events. Conclusions: A high oxHDL/apoAI was associated with the presence of HRP and significant stenosis determined by coronary CT angiography, which can lead to cardiovascular events in patients with suspected stable CAD. Highlights: High oxHDL/apoAI may be involved in high-risk coronary plaque characteristics. The oxHDL/apoAI may be associated with cardiovascular events. The oxHDL/apoAI is a potential biomarker in cardiovascular events.